Parent Knowledge and Preferences of Language Learning and Use in an International School in Viet Nam - Clayton Lehman, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Although there is a growing base of literature about international schools, there is little research dedicated to studying the parents of students attending international schools. The purpose of this study was to explore English language learner (ELL) parent knowledge and preferences of language learning and use at an English-medium international school in Ho Chi Minh City, Vietnam. Within the study, the researcher compared the differences in parent knowledge and preferences of language learning and use between local parents and expatriate parents of students enrolled in an ELL program. Areas explored in the study were language learning and language use within the school, including language policy. Data acquisition for this quantitative study occurred through a survey completed by 134 parents of ELL students enrolled in an international school in Ho Chi Minh City, Vietnam. The main findings of this research study revealed there were significant differences between local ELL parents and expatriate ELL parents concerning knowledge and preferences of language learning and use at that international school.Received 26th February 2020; Revised 12thAugust 2020; Accepted 20th September 2020